Design of NDI-SMC based robust hybrid nonlinear controller for load following operation in pressurized water reactor - Yadav, Deepak Kumar; Gupta, Amitava; Munshi, Prabhat (Nuclear engineering and design, 2020)
•NDI plus SMC based robust controller is designed for PWR core.•Xenon oscillation is considered.•Robustness of NDI plus SMC controller over single NDI controller has been proved and demonstrated for PWR core.•Varying range of parametric uncertainty and external disturbances has been considered. The pressurized water reactor (PWR) is a natural choice for the load following operation due to its inherent self-regulating nature. The nonlinear mathematical model of PWR is derived considering the large parametric uncertainties due to power variation, Xenon oscillations and external disturbances in the reactor core. This paper proposes a robust and tracking hybrid nonlinear state feedback tracking controller which combines nonlinear dynamic inversion (NDI) and the sliding mode control (SMC) algorithm to achieve a smooth load following operation for such complex system. The proposed nonlinear controller is able to ensure satisfactory performances e.g. smooth tracking of reference power and nullify the xenon oscillations in PWR core. This designed controller is also capable to satisfy the limits of the variables like (a) zonal coolant temperature, (b) average fuel temperature and (c) external control rod reactivity for such system in PWR core during the operation. The performance of the proposed nonlinear controller is further compared with the single NDI based controller to show the effectiveness of the proposed methodology against the varying parametric uncertainties and external disturbances. This paper demonstrates the simulation results using Matlab/Simulink platform.